Knowledge of congenital cytomegalovirus (CMV) in pregnant women in Australia is low, and improved with education. (26th April 2019) - Lazzaro, Amanda; Vo, Mai Linh; Zeltzer, Justin; Rawlinson, William; Nassar, Natasha; Daly, Kate; Lainchbury, Anne; Shand, Antonia
Abstract : Background: Cytomegalovirus (CMV) is the most common congenital infection and can cause hearing loss and neurodevelopmental disability in infected infants. International research shows women have limited knowledge about CMV. Aims: To assess pregnant women's knowledge and attitudes about CMV before and after provision of information. Materials and Methods: Cross‐sectional survey of pregnant women between November 2017 and February 2018 at two Australian hospitals. Participating women completed an initial survey on maternal characteristics, knowledge of infections, and CMV risk behaviours. Participants were then given an information leaflet and completed a follow‐up survey. Results: Four hundred and fifty‐seven women completed the initial survey, of whom 73/457 (16%) had heard of CMV. Behaviours increasing risk of CMV transmission were common: 58% reported regularly kissing their child on the lips; 57% did not always wash their hands after changing a wet nappy. Knowledge about CMV significantly improved after reading the leaflet in the 145 women completing the follow‐up survey. More women correctly identified that CMV could cause deafness in a baby (35% before, 85% after), was spread by saliva (38% vs 94%) or urine (27% vs 86%) and prevented by hand‐washing (55% vs 99%; all P < 0.001). Conclusion: Knowledge about CMV was low in pregnant women. An educational leaflet was effective in improving knowledge.